Book review - Best laid plans: women coming of age in uncertain times, by Jessica Halliday Hardie. Oakland: University of California Press, 2022. 274 pp. $29.95 paper. ISBN: 9780520297883 - Syed Hussien, Sh Fatimah Alzahrah (American Sociological Association, 2024)
In the time of unprecedented global uncertainty that we are experiencing today, the life trajectories of youth coming of age is of particular interest. How can we ensure young people are given equal opportunities to succeed as they transition into adulthood? Social conditions undoubtedly affect the experiences of youths transitioning into adulthood and life opportunities available to them. Yet at the individual level there is also a focus on the aspirations and ability of young people to plan well for their futures. The neoliberal perspective tends to focus on the abilities of individuals to beat the odds. Can young people plan well enough to ensure their success? A more balanced conversation would then expand into the interaction between the social and the individual in understanding the outcomes of youth coming of age.